Ambient dose equivalent rate from 137Cs and natural radionuclides in one-story residential buildings in settlements of the Bryansk region in 2020–2021 - V. P. Ramzaev; A. N. Barkovsky; A. A. Bratilova (Радиационная гигиена)
Method of in situ gamma-ray spectrometry was used to discriminate contributions of 137Cs and natural radionuclides to ambient dose equivalent rate indoors in settlements located in the zones of radioactive contamination after the Chernobyl accident. The measurements using a portable scintillation gamma spectrometer-dosimeter were carried out in 115 individual one-story residential buildings in 46 settlements of the Bryansk region of Russia in the summer period of 2020–2021. According to official data, the average density of soil contamination with 137Cs in the settlements ranged from 27 to 533 kBq/m2. Based on the type of building materials that had been used to construct the walls, the surveyed houses were divided into three large groups: wooden (walls made of logs) – 51 buildings, stone (walls built of bricks and/or concrete panels) – 34 buildings, and frame-panel – 30 buildings. The latter had walls constructed of wooden panels with the inclusion of heat-insulating material. Outside, the walls of the frame-panel houses were lined with a layer of silicate (white) bricks. 70 houses were built before the accident and 37 – after the accident. In eight cases it was not possible to reliably estimate the period of construction. The total ambient dose equivalent rate ranged from 42 to 228 nSv/h (average = 77 nSv/h). The values of the ambient dose equivalent rate from natural radionuclides were in the range 27–122 nSv/h. The average values of the ambient dose equivalent rate from natural radionuclides in the groups of wooden, frame-panel, and stone houses were 42, 42 and 58 nSv/h, respectively. The difference between stone houses and panel houses was statistically significant (P < 0.01). The same difference was found between stone houses and wooden houses (P < 0.01). The average values of the ambient dose equivalent rate from 137Cs, normalized to the density of soil contamination with 137Cs, were 0.13, 0.16, and 0.05 (nSv/h)/(kBq/m2) in wooden, frame-panel, and stone houses, respectively. The normalized ambient dose equivalent rates from 137Cs in the group of stone houses were statistically significantly (P < 0.01) lower compared to the corresponding values for the groups of wooden houses and frame-panel houses. The small differences between frame-panel and wooden houses turned out to be statistically significant (P < 0.05). The median and mean values of the normalized ambient dose equivalent rate from 137Cs for houses built before the accident were lower compared to those for houses built after the accident. These differences were statistically significant (P < 0.01) for all groups of houses. The mean values of the normalized ambient dose equivalent rate from 137Cs and the ambient dose equivalent rate from natural radionuclides obtained in this study can be used to estimate the external effective dose to a person staying inside a one-story residential building. In this case, one should take into account not only the type of building materials used to construct the house, but also the time period of the construction: before or after the Chernobyl accident.